Lead removal from crude antimony in the pyrometallurgical refining process by using NaPO3 - YE Long-gang; YANG Sheng-hai; TANG Chao-bo; TANG Mo-tang (工程科学学报)
In order to solve the problem of lead removal from crude antimony in the traditional antimony refining process,NaPO3 was introduced as a lead elimination reagent to generate phosphate slag and the slag was removed by floating on the surface of liquid antimony. The reaction mechanisms were clarified by thermogravimetric-differential thermal analysis and X-ray diffraction analysis and removal of Pb from crude Sb was investigated by condition experiment. It is found that PbO and NaPO3 begin an endothermic reaction at 590℃ and mainly form NaPb4(PO4)3 and NaPbPO4 below 850℃ and above 850℃,respectively. The reaction products of the mixture of PbO,Sb2O3 and NaPO3 show that NaPO3 preferentially reacts with PbO when NaPO3 is insufficient,and amorphous antimony glass will generate only with enough NaPO3. Single-factor experiments were taken with NaNO3 as an oxidizing agent under nitrogen.Reaction time,temperature,NaPO3 and NaNO3 amounts were considered for smelting results. Under the optimal condition,the content of lead in refined antimony is 0. 047% and 98. 90% of lead is removed.